PERANCANGAN SISTEM INFORMASI AKUNTANSI PERSEDIAAN BAHAN BAKU MAKANAN TERNAK PADA BAGIAN GUDANG DI KSU TANDANGSARI SUMEDANG - Abdillah, Junaedi (Program Studi Akuntansi FPEB UPI, 2017)
System storage of fodder raw material inventory in the warehouse still done manually record it in a book Raw Materials Inventory so the recording process takes longer. In addition, it can also errors in the information at the time of recording. Based on the analysis of the obstacles that exist in the Parts Warehouse, the authors build a database-based applications using Microsoft Office Access 2013 that can handle the entire data on revenues, expenditures and request for raw materials, and produce information accurately and automatically. Systems development method waterfall method, the tools used in the analysis of system design is Flowmap, Context Diagram, Data Flow Diagram, Data Dictionary and Relation Table. While the implementation of the system design is the programming language Visual Basic for Application (VBA) by using Microsoft Office Access 2013 as the database.